THE INFLUENCE OF PROJECT MANAGEMENT KNOWLEDGE ON THE SUCCESSFUL CONSTRUCTION IMPLEMENTATION: Case Study On Building "X" Construction - Giovan M Fiecky, Zahrandy; A.A BGS. Dinariyana Dwi , Putranta (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2024)
Current scientific developments in project management can be compared with other fields of management science. One of the important points in scientific analysis of project management is the study of the level of success of a project. This paper tries to examine the level of project success based on aspects of project management knowledge. The study was carried out at a company that was working on the construction of a building. The 14 aspects of project management knowledge were developed to see how each aspect contributes to the success of a project. 70 respondents who were involved in construction projects were the objects of this research. PLS SEM is used as an analytical tool to see the contribution of project knowledge aspects to project success. It was concluded that the 3 aspects that contributed most to project success were Project Financial Management, Project Claims Management and Project Communication Management.